Analysis of manganes deposits of Leg 23 - Robert B Whitmarsh; Oscar E Weser; David A Ross; A Syed; J E Boudreaux; R G Coleman; R L Fleisher; R W Girdler; D Jipa; Robert B Kidd; Tapas Kumar Mallik; Frank T Manheim; et al. (PANGAEA, 1974)
Located on the Arabian Abyssal Plain near its southernmost termination, this site recorded continuous Middle Eocene through Pleistocene deep-water sedimentation above oceanic basalt. A chert layer is developed at the base of the Eocene strata. The Eocene through Miocene sequence shows the transition from biogenic ooze to brown clay sedimentation which typifies depositional sites as they move from a ridge crest to a deep-ridge flank position. Above this sequence is an undifferentiated Pliocene-Miocene through Pleistocene interval of terrigenous and calcareous turbidites. The former were derived from the Indus Canyon, and the latter from elsewhere.
Supplement to: Whitmarsh, RB et al. (1974): Site 221. In: Whitmarsh, R.B.; Weser, O.E.; Ross, D.A.; et al., Initial Reports of the Deep Sea Drilling Project, Initial Reports of the Deep Sea Drilling Project, U.S. Government Printing Office, XXIII, 167-210, https://doi.org/10.2973/dsdp.proc.23.105.1974